2010
DOI: 10.1007/s12272-010-0401-4
|View full text |Cite
|
Sign up to set email alerts
|

Two new hetero-spirocyclic γ-lactam derivatives from marine sediment-derived fungus Aspergillus sydowi D2–6

Abstract: Two new hetero-spirocyclic gamma-lactams, azaspirofurans A (1) and B (2), had been isolated from a marine sediment-derived fungus Aspergillus sydowi D2-6. Their structures were determined by the chemical evidence and spectral analyses. Compound 1 exhibited cytotoxicity against A549 cell line with the IC50 value of 10 microM by MTT method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 8 publications
0
36
0
1
Order By: Relevance
“…Fractionation and multiple steps of SiO 2 and Sephadex LH-20 followed by reversed phase semi-preparative HPLC purification led to the isolation and identification of a new metabolite belonging to the diketopiperazine family named brevianamide X 1 ( Figure 1 ), in addition to the known metabolites brevianamide F 4 , cyclo( L -pro- L -val), cyclo( L -pro- L -ile), cyclo( L -pro- L -phe), cyclo( L -pro- L -leu), fumitremorgin C, spirotryprostatin A, 6-methoxy-spirotryprostatin C (El-Gendy and Rateb, 2015), pseurotin A (Rateb et al, 2013), bis (dethio) bis (methylthio)gliotoxin (Afiyatullov et al, 2005), and azaspirofurans A and B (Ren et al, 2010). These metabolites were identified based on comparing their spectral data with published data.…”
Section: Resultsmentioning
confidence: 99%
“…Fractionation and multiple steps of SiO 2 and Sephadex LH-20 followed by reversed phase semi-preparative HPLC purification led to the isolation and identification of a new metabolite belonging to the diketopiperazine family named brevianamide X 1 ( Figure 1 ), in addition to the known metabolites brevianamide F 4 , cyclo( L -pro- L -val), cyclo( L -pro- L -ile), cyclo( L -pro- L -phe), cyclo( L -pro- L -leu), fumitremorgin C, spirotryprostatin A, 6-methoxy-spirotryprostatin C (El-Gendy and Rateb, 2015), pseurotin A (Rateb et al, 2013), bis (dethio) bis (methylthio)gliotoxin (Afiyatullov et al, 2005), and azaspirofurans A and B (Ren et al, 2010). These metabolites were identified based on comparing their spectral data with published data.…”
Section: Resultsmentioning
confidence: 99%
“…pseurotins D (82) displayed an apomorphine-antagonistic effect [73], as well as antiparasitic and cytotoxicity affects [78], and pseurotins F2 (83) demonstrated apomorphine-antagonistic activity [86] and chitin synthase inhibition [74]. Screening for antitumor agents, the marine-sediment-derived fungus Aspergillus sydowii D2-6 was found to produce two new 3-STAs, named azaspirofurans A and B (84 and 85), which feature a new furan ring instead of the long linear side chain of pseurotin [87]. In vitro cytotoxicity experiments have demonstrated that 85 has moderate cytotoxicity toward A549 HTCL (IC50 = 10 μM) [87].…”
Section: -Spirotetramic Acidsmentioning
confidence: 99%
“…Chiral amino acid and amino esters are important compounds used as precursors in the preparation of various pharmaceutical and agrochemical molecules, particularly chiral γ‐amino acids, γ‐lactams, and δ‐amino alcohols, which are building blocks for pharmaceutical substances in the chemical industry . Moreover, amino acids have important applications in various organic syntheses as chiral starting materials, auxiliaries, polymer sources, and catalysts.…”
Section: Introductionmentioning
confidence: 99%